Determinants of health related quality of life in patients with chronic obstructive pulmonary disease in Chitwan, Nepal - Sharma, Kalpana; Sharma, Muna; Joshi, Sarala (Journal of Chitwan Medical College, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a growing cause of morbidity and mortality worldwide. However, the determinants and its impact on Health Related Quality of Life (HRQL) are not well-studied in Nepal. This study aimed to assess the determinants of HRQL in patients with COPD in Chitwan, Nepal. Methods: Cross-sectional study was conducted in outpatient departments of two medical colleges and two governmental hospitals of Chitwan district. A stratified proportionate sampling technique was used to select 470 patients suffering from COPD for at least 3 months and data were collected using pretested HRQL instruments. Linear regression model was constructed to identify the determinants of HRQ. Results: The mean age patients was 68.64 (±10.25 SD) years and 54.0% were female. The mean score and standard deviation of total HRQL was 55.84 ± 11.21, while 54.10 ±13.95 was for physical, 56.69 ±13.73 for social and 56.96 ±12.05 for psychological components respectively, showing higher impairment on physical health. Dyspnea (β = -0.301, p = <0.001), perceived health status (β = 0.264, p<0.011), financial difficulties for treatment (β = -0.195, p = <0.011), regular follow-ups (β = -0.116, p = 0.001), age (β = -0.101, p = 0.006) and exacerbations (β = -0.098, p = 0.008) were the notable determinants of HRQL. In addition, other predictors of HRQL were smoking status, duration of illness, and exposure to dust & smoke in work place. Conclusions: Patients with COPD have impaired HRQL. Hence, attention should be paid by nurses and health care planner on enhancing HRQL by addressing notable determinants while treating them in health care setting.